An Analysis of Students’ Difficulties in Comprehending Descriptive Text at SMPN 2 Galesong Utara - Anilza Seftiya; Maemunah Muhayyang; Chairil Anwar Korompot (State University of Makassar, 2025)
This research aimed to identify the factors contributing to students' difficulties in comprehending descriptive texts at SMPN 2 Galesong Utara. A descriptive qualitative research design was employed, focusing on Grade 8 students during the 2023/2024 academic year. The study sample comprised 30 students from class 8E, selected through purposive sampling. Data collection was conducted through interviews. The researcher found that there were various difficulties encountered by the students in comprehending descriptive text, namely (1) understanding long sentence in the text, (2) inadequate instruction presented by teacher, (3) understanding vocabulary, and (3) house and school environment. In conclusion, there are 3 factors causing students in comprehending descriptive text at SMPN 2 Galesong Utara. Keywords: Difficulty, Comprehension, Descriptive Text